Light directs zebrafish period2 expression via conserved D and E boxes. - Gad Vatine; Daniela Vallone; Lior Appelbaum; Philipp Mracek; Zohar Ben-Moshe; Kajori Lahiri; Yoav Gothilf; Nicholas S Foulkes (PLoS Biology)
For most species, light represents the principal environmental signal for entraining the endogenous circadian clock. The zebrafish is a fascinating vertebrate model for studying this process since unlike mammals, direct exposure of most of its tissues to light leads to local clock entrainment. Importantly, light induces the expression of a set of genes including certain clock genes in most zebrafish cell types in vivo and in vitro. However, the mechanism linking light to gene expression remains poorly understood. To elucidate this key mechanism, here we focus on how light regulates transcription of the zebrafish period2 (per2) gene. Using transgenic fish and stably transfected cell line-based assays, we define a Light Responsive Module (LRM) within the per2 promoter. The LRM lies proximal to the transcription start site and is both necessary and sufficient for light-driven gene expression and also for a light-dependent circadian clock regulation. Curiously, the LRM sequence is strongly conserved in other vertebrate per2 genes, even in species lacking directly light-sensitive peripheral clocks. Furthermore, we reveal that the human LRM can substitute for the zebrafish LRM to confer light-regulated transcription in zebrafish cells. The LRM contains E- and D-box elements that are critical for its function. While the E-box directs circadian clock regulation by mediating BMAL/CLOCK activity, the D-box confers light-driven expression. The zebrafish homolog of the thyrotroph embryonic factor binds efficiently to the LRM D-box and transactivates expression. We demonstrate that tef mRNA levels are light inducible and that knock-down of tef expression attenuates light-driven transcription from the per2 promoter in vivo. Together, our results support a model where a light-dependent crosstalk between E- and D-box binding factors is a central determinant of per2 expression. These findings extend the general understanding of the mechanism whereby the clock is entrained by light and how the regulation of clock gene expression by light has evolved in vertebrates.